Simultaneous range and velocity measurement using frequency shifted feedback laser - Shinichi Oshima; Yoshito Isei (Measurement: Sensors, 2021)
A laser Doppler velocimeter (LDV) is a useful sensor for measuring the velocity and length of steel products. However, the distance to the measurement target is restricted to the intersection region of the two laser beams, making it difficult to measure steel products with large distance fluctuations and dimensional ranges. To remove this restriction, a new non-contact distance and velocity sensor FSFL-RVM (frequency shifted feedback laser range and velocity meter) employing FSFL, whose frequency changes proportionally to the time at ultra-high speed, was developed. Its measurement principle and accuracy were evaluated using a rotating disk, confirming its ability to measure velocities with the same accuracy as the LDV in a distance range 5 times the measurement distance range of the LDV and simultaneously measure distances with the accuracy within 0.1 mm.